Dexmedetomidine Mitigates Microglial Activation Associated with Postoperative Cognitive Dysfunction by Modulating the MicroRNA-103a-3p/VAMP1 Axis - Zhichao Wu; Han Wang; Zuan Shi; Yalan Li (Neural Plasticity)
Surgery-induced microglial activation is critical in mediating postoperative cognitive dysfunction (POCD) in elderly patients, where the important protective effect of dexmedetomidine has been indicated. However, the mechanisms of action of dexmedetomidine during the neuroinflammatory response that underlies POCD remain largely unknown. We found that lipopolysaccharide (LPS) induced substantial inflammatory responses in primary and BV2 microglial cells. The screening of differentially expressed miRNAs revealed that miR-103a-3p was downregulated in these cell culture models. Overexpression of miR-103a-3p mimics and inhibitors suppressed and enhanced the release of inflammatory factors, respectively. VAMP1 expression was upregulated in LPS-treated primary and BV-2 microglial cells, and it was validated as a downstream target of miR-103-3p. VAMP1-knockdown significantly inhibited the LPS-induced inflammatory response. Dexmedetomidine treatment markedly inhibited LPS-induced inflammation and the expression of VAMP1, and miR-103a-3p expression reversed this inhibition. Moreover, dexmedetomidine mitigated microglial activation and the associated inflammatory response in a rat model of surgical trauma that mimicked POCD. In this model, dexmedetomidine reversed miR-103a-3p and VAMP1 expression; this effect was abolished by miR-103a-3p overexpression. Taken together, the data show that miR-103a-3p/VAMP1 is critical for surgery-induced microglial activation of POCD.